(untitled) (International Educators Conference, 2025)
In infants and children, the urinary tract is a relatively common site of infection. Urinary tract infections (UTIs) result in significant acute morbidity as well as long-term medical problems including delayed hypertension and progressive renal dysfunction. Accurate diagnosis and timely treatment are vital in limiting these long-term sequelae, because the pediatric kidney is particularly susceptible to scarring and permanent renal damage.